Fatty acylCoA synthetase FadD13 regulates proinflammatory cytokine secretion dependent on the NF‐κB signalling pathway by binding to eEF1A1. (9th August 2019) - Wei, Sha; Wang, Dianbing; Li, Hua; Bi, Lijun; Deng, Jiaoyu; Zhu, Guofeng; Zhang, Jibin; Li, Chuanyou; Li, Min; Fang, Yuan; Zhang, Guimin; Chen, Jian; et al.
Abstract: Mycobacterium tuberculosis (Mtb) manipulates multiple host defence pathways to survive and persist in host cells. Understanding Mtb–host cell interaction is crucial to develop an efficient means to control the disease. Here, we applied the Mtb proteome chip, through separately interacting with H37Ra and H37Rv stimulated macrophage lysates, screened 283 Mtb differential proteins. Through primary screening, we focused on fatty acylCoA synthetase FadD13. Mtb FadD13 is a potential drug target, but its role in infection remains unclear. Deletion of FadD13 in Mtb reduced the production of proinflammatory cytokines IL‐1β, IL‐18, and IL‐6. Bimolecular fluorescence complementation and colocalization showed that the binding partner of FadD13 in macrophage was eEF1A1 (a translation elongation factor). Knockdown eEF1A1 expression in macrophage abrogated the promotion of proinflammatory cytokines induced by FadD13. In addition, Δ fadD13 mutant decreased the expression of the NF‐κB signalling pathway related proteins p50 and p65, so did the eEF1A1 knockdown macrophage infected with H37Rv. Meanwhile, we found that deletion of FadD13 reduced Mtb survival in macrophages during Mtb infection, and purified FadD13 proteins induced broken of macrophage membrane. Taken together, FadD13 is crucial for Mtb proliferation in macrophages, and it plays a key role in the production of proinflammatory cytokines during Mtb infection.